Supply chain network equilibrium considering coordination between after-sale service and product quality. (January 2023) - Xiao, Ya-Xuan; Zhang, Ren-Qian
Abstract: In a highly integrated supply chain system, the trade-off between after-sale service and product quality becomes an important consideration in establishing and maintaining a sustainable supply chain partnership. To this end, we proposed an underlying decentralized supply chain network (DSCN) equilibrium model for service-quality coordination under capacity constraints and demand uncertainty. The proposed DSCN model is compared with centralized supply chain network (CSCN). Then, the buyback contract is introduced to coordinate the DSCN. After the implementation of supply chain network equilibrium (SCNE) in numerical examples, we obtain the equilibrium solution of the proposed model. The result shows that, compared with DSCN, CSCN does not always provide better service or product quality. Moreover, by introducing the buyback contract, the equilibrium profits of DSCN are improved, so that the Pareto improvement occurs. Our findings can provide useful analytical frameworks and implications for how to coordinate after-sale service, product quality, selling price, and product ordering decisions in the supply chain network simultaneously. Highlights: Interaction of service and product quality on supply chain performance are analyzed. Alternative variational inequality is formulated in DSCN and CSCN, respectively. Equilibrium conditions of DSCN and optimality condition of CSCN are compared. Pareto improving of DSCN occurs after introducing the buyback contract. Equilibrium solutions and conclusions are both derived from the numerical examples.